Cultural Contestation in Ethnic Conflict - Ross, Marc Howard (Cambridge University Press, 2013)
What are long-term ethnic conflicts about? How do they develop? Why are they so intense and hard to settle? Why do opposing sides view and describe what are ostensibly the same events so differently? How does identity shape why and how ethnic conflict is waged? What do good settlements look like?